2015
DOI: 10.1007/s10898-015-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

A proximal alternating direction method of multipliers for a minimization problem with nonconvex constraints

Abstract: In this paper, a proximal alternating direction method of multipliers is proposed for solving a minimization problem with Lipschitz nonconvex constraints. Such problems are raised in many engineering fields, such as the analytical global placement of very large scale integrated circuit design. The proposed method is essentially a new application of the classical proximal alternating direction method of multipliers. We prove that, under some suitable conditions, any subsequence of the sequence generated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…where κ > 0 and η ∈ (0, 1) are fixed parameters. If inequalities (20) are satisfied, then τ n+1 = βτ n for some β > 1. Otherwise, we put τ n+1 = τ n .…”
Section: The Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
See 4 more Smart Citations
“…where κ > 0 and η ∈ (0, 1) are fixed parameters. If inequalities (20) are satisfied, then τ n+1 = βτ n for some β > 1. Otherwise, we put τ n+1 = τ n .…”
Section: The Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
“…Remark 4. Let us explain the motivation behind criterion (20) for increasing the penalty parameter. Multiple numerical experiments with fixed penalty parameter τ demonstrated that one needs to increase τ only if the infeasibility measure S i x n i − y n i − c i , i ∈ {1, 2}, does not decrease with iterations.…”
Section: The Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
See 3 more Smart Citations